Efficient Activation of Nanomechanical Resonators. (21st October 2018) - Hafiz, Md. Abdullah Al; Jaber, Nizar; Kazmi, Syed Naveed Riaz; Hasan, Mohammad; Alsaleem, Fadi; Younis, Mohammad
Abstract: Electrostatically transduced nano‐electromechanical system resonators operating in the very high and ultra‐high frequency bands are promising for many practical applications. However, electrostatically transduced nanoscale devices commonly suffer from poor transduction efficiency due to the reduced capacitive area for actuation and detection. Also, the requirement of ultra‐high actuation forces renders exploitation of their higher‐order vibration modes and the desirable nonlinear behaviors practically beyond reach. Hence, it is imperative to develop a methodology that efficiently actuates nano and sub‐micrometer scale highly stiff resonators with low voltages available in a standard integrated circuit. Here, the utilization of the passive voltage amplification across the inductor of an inductor–capacitor LC tank resonant circuit to efficiently actuate nanoresonators with high forcing amplitude is proposed and demonstrated. The proposed technique is simple and flexible in its implementation, and does not require any active electronic components. A forcing amplification up to 19 times (≈25 dB) is experimentally shown, which can be improved further by reducing the electrical damping in the tank circuit. In addition, two independent ports on the same device for force amplification are shown, which, if simultaneously activated, can increase the overall forcing amplitude by an order of magnitude exceeding hundreds of amplification gain. Abstract : An LC tank circuit is employed to passively amplify the force to activate nonlinear resonances of mechanically stiff micro/nanoresonators. The proposed technique is simple and flexible to implement, which paves the way for more aggressive research on the utilization of high‐frequency nano‐electromechanical systems (NEMS) resonances for practical applications and facilitates the exploration of nonlinear dynamics in NEMS devices.